1,3,4-Thiadiazole Scaffold: As Anti-Epileptic Agents - Anthwal, Tulika; Nain, Sumitra (Frontiers in Chemistry, 2022)
A wide range of biological activities is exhibited by 1,3,4-thiadiazole moiety such as anti-diabetic, anti-cancer, anti-inflammatory, anti-convulsant, anti-viral, anti-hypertensive, anti-microbial. To date, numerous drugs are available in the market such as Butazolamide, Sulfamethoxazole, Acetazolamide. Several modifications have been done in the 1,3,4-thiadiazole moiety which showed good potency as anticonvulsant agents which are highly effective and have less toxicity. After An depth literature survey in this review, we have compiled various derivatives of 1,3,4-thiadiazole scaffolds which have been synthesized as anticonvulsant agents.